Pemetaan Tingkat Kematangan Sistem Inovasi Daerah Peternakan di Kabupaten Lima Puluh Kota - Amna Suresti; Uyung Gatot S Dinata; James Hellyward; Rahmi Wati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
This study aims to analyze the potential for the development of the livestock sector based on innovation system reinforcement by looking at maturity level condition of the existing innovation system in Lima Puluh Kota . The method used is ANIS with the Expert Opinion Survey. The results showed that the average value of maturity level towards innovation system of the livestock sector in Lima Puluh Kota regency was 2.56 means that the maturity level towards innovation system of the livestock sector in Lima Puluh Kota Regency still in the developing position 1.5 to 3 has still not been established yet 3 to 4. At the macro level for policy, it obtained an average value 2.62, average value of messolevel 2.41 for institutional, average value of messo level 2.56 for program and the average value 2.66 for the highest micro level. Keywords: Innovation Systems, Analysis of National Innovation Systems, Expert Opinion Survey